Selective Laser Trabeculoplasty: An Overview - Jha, Bhaskar (J Curr Glaucoma Pract, 2012)
Given the obvious quality of life concerns with medical and surgical lowering of intraocular pressure (IOP), lasers have received considerable attention as a therapeutic modality for glaucoma. Selective laser trabeculoplasty (SLT) is increasingly being used in clinical practice as both the primary procedure and as an adjunct to medical and surgical therapy. Preliminary published evidence suggests that SLT is an effective, compliance-free, repeatable and safe therapeutic modality having only minor, transient, self-limiting or easily controlled side effects with no sequelae. This review attempts a broad overview of the current knowledge of its mechanism, efficacy, indications and limitations, point out the knowledge lacunae that still exist with respect to this highly promising technology which has captured the attention of glaucoma surgeons all over the world. HOW TO CITE THIS ARTICLE: Jha B, Bhartiya S, Sharma R, Arora T, Dada T. Selective Laser Trabeculoplasty: An Overview. J Current Glau Prac 2012;6(2):79-90.